2020
DOI: 10.1101/2020.04.14.041731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chloroquine Kills Hair Cells in Zebrafish Lateral Line and Murine Cochlear Cultures: Implications for Ototoxicity

Abstract: 22 98195-7420 23 24

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This observation is in line with a recent study showing that chloroquine specifically damages OHCs in mice (Davis et al, 2020). The aggravating effect of chloroquine was also found in Kv7.4 Q71fs (Fig.…”
Section: Inhibition Of the Basal Autophagy Aggravates The Cytotoxicitysupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in line with a recent study showing that chloroquine specifically damages OHCs in mice (Davis et al, 2020). The aggravating effect of chloroquine was also found in Kv7.4 Q71fs (Fig.…”
Section: Inhibition Of the Basal Autophagy Aggravates The Cytotoxicitysupporting
confidence: 93%
“…3), it is conceivable that the basal endogenous autophagy activity in OHCs may be kept at a relatively high level in order to counteract the cytotoxicity associated with the large expression of the Kv7.4 protein. Consistent with such views, an autophagy inhibitor, chloroquine, is reported to induce hair cell loss (Davis et al, 2020). Hair cell loss was also found in conditional autophagy-deficient mice (Fujimoto et al, 2017).…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 61%
“…Hence, these findings could indicate the onset of effects on cochlear structures, especially OHCs, before they are reflected in audiometric results (18). However, the effect of HCQ on OHCs can depend on the dose and duration of use (11). In this study, 80% of the patients used HCQ for 5 days, and only two patients continued to take the drug for 6 days as symptoms persisted.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the COVID-19 period, numerous patients have used HCQ, especially at the beginning of a pandemic (8)(9)(10). Although a recent study showed hair cell damage after exposure to chloroquine (CQ)/HCQ in zebrafish lateral line and neonatal mouse cochlear cultures, this drop was significantly dose dependent (11). In the human domain, most of the studies that reported the ototoxic effects of HCQ on the auditory system and balance in treating other diseases were case reports and were prescribed at different doses and durations (8,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation